2020
DOI: 10.1080/13506285.2020.1714825
|View full text |Cite
|
Sign up to set email alerts
|

Word predictability depends on parafoveal preview validity in Chinese reading

Abstract: Research with alphabetic scripts shows that providing an invalid parafoveal preview eliminates or diminishes effects of contextual predictability on word identification, revealing that such effects depend on the interplay between top-down contextual expectations and bottom-up perceptual information. Whether similar effects are observed character-based scripts like Chinese is unknown. However, such knowledge would extend our understanding of contextual prediction in different writing systems. Accordingly, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…cahc), and eliminated for orthographically dissimilar previews (e.g. pies; Balota, Pollatsek, & Rayner, 1985;see Staub, 2015), with similar effects for Chinese (Chang et al, 2020). These findings suggest that, in high-predictability contexts, readers assess the fit of parafoveal information with their expectations.…”
Section: Introductionmentioning
confidence: 87%
“…cahc), and eliminated for orthographically dissimilar previews (e.g. pies; Balota, Pollatsek, & Rayner, 1985;see Staub, 2015), with similar effects for Chinese (Chang et al, 2020). These findings suggest that, in high-predictability contexts, readers assess the fit of parafoveal information with their expectations.…”
Section: Introductionmentioning
confidence: 87%
“…Staub and Goddard (2019), following up on patterns in previous studies such as Balota, Pollatsek, and Rayner (1985) and Reingold, Reichle, Glaholt, and Sheridan (2012), found that when the boundary paradigm (Rayner, 1975) is used to deny the reader parafoveal preview of a target word until it is directly fixated, the predictability of the target word no longer has an influence on early eye movement measures, while the frequency effect persists. The lack of predictability effect with invalid preview has now been replicated in Chinese reading (Chang et al, 2020), as well as in an eye movement corpus study (Luke, 2018) using the moving window paradigm (McConkie & Rayner, 1975). Thus, predictability may have most or all of its effect while a word is being viewed parafoveally, before it is directly fixated, while frequency also influences processes that occur during foveal viewing.…”
mentioning
confidence: 87%
“…It appears that these expectations constrain lexical identification online during natural reading. To be clear, we have demonstrated that both higher order sources of semantic information (obtained from text to the left of fixation) and lower level perceptual and relatively shallow linguistic sources of information (obtained from upcoming text to the right of fixation) exert a direct and relatively immediate influence on word identification as we read ( Chang, Zhang, et al, 2020 ; Staub & Goddard, 2019 ). Our results are a clear illustration of concurrent top-down and bottom-up constraints in operation during sentence processing.…”
Section: Discussionmentioning
confidence: 90%